Spray penetration into asparagus (Asparagus officinalis L.) canopy using different nozzle inclinations and application rates - Vásquez-Castro, J. (2020)
Asparagus (Asparagus officinalis L.) is a difficult crop to treat with spraying pesticides because its architecture makes it difficult for droplets to penetrate inside of the canopy, where its pests are located. This study aims to examine the influence of operational parameters, such as nozzle inclination and application rates on the inner side of the canopy. We installed nozzles in the spray boom and its droplegs in three different inclinations: 0° with the plant, 30° in the direction of movement of the tractor-sprayer assembly (+30°), and 30° in the opposite direction (−30°). We applied the mixture in application rates of 600, 900, and 1,200 L ha−1. More so, the regulation used by the farmer of 0° and 800 L ha−1 was applied as a control. Copper (Cu) was used as a tracer for the mixture in a dose of 13.5 g ha−1. Also, non-plasticized polyvinyl chloride grooved tubes (PVC) were installed inside the asparagus canopy and polyethylene sheets were placed on the pipes at different heights from the ground. Later, we analyzed the sheets with atomic absorption spectrophotometry. Results showed that the nozzle inclination and sampling height had notable effects on the copper deposit. Conversely, different application rates showed no varied effects significantly. The greatest copper deposition in the asparagus canopy was achieved with a nozzle inclination of +30° with any application rate. Finally, we recommend regulating the sprayers with a nozzle inclination of +30° and an application rate of 600 L ha−1 as the most effective adjustment for the distribution of pesticides and represent the lowest cost of operation since there is no influence of the application rate.